Multicriteria evaluation tools to support the conceptual design of activated sludge systems. - Flores, X; Bonmatí, A; Poch, M; Roda, I; Jiménez, L; Bañares-Alcántara, R (2007)
During the past decade the pressure of the whole spectrum of stakeholders has increased considerably leading the consideration of different types of objectives, i.e. economical, technical, legal and environmental, into the process design efforts. Thus, the traditional design approaches should turn into more complex assessment methods including different types of objectives in order to conduct integrated assessments. The objective of this paper is to present and discuss the usefulness of three evaluation tools, based on multicriteria decision analysis, to support the conceptual design of activated sludge systems These support tools consist of: i) preliminary multiobjective optimization, where the most promising options (those located near to the optimum) are compared based on the results of dynamic simulation, ii) identification of strong and weak points for each option by means of classification trees and the subsequent extraction of knowledge-based rules, and iii) evaluation of the trade-offs between a certain evaluation criteria and the overall process performance through the integrated application of mathematical modelling and qualitative knowledge extracted during the design process.